The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1055/s-0036-1593502
|View full text |Cite
|
Sign up to set email alerts
|

Bienengift in der Komplementärmedizin

Abstract: Summary Bienenprodukte wurden bereits in der Antike medizinisch genutzt. Seit einigen Jahrzehnten r?ckt besonders die Anwendung von Honig wieder in den Fokus der medizinischen Forschung, u.a. wegen seiner antibakteriellen und antimikrobiellen Wirkung z. B. bei der Wundheilung oder hinsichtlich seines m?glichen Potenzials bei der Bek?mpfung multiresistenter Bakterienst?mme. Der Begriff ?Apitherapie? umfasst jedoch mehr als den Einsatz von Medizinalhonig. Apitherapie beinhaltet die medizinische Anwendung aller B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Remarkably, Domerego and Hainbuch suggested different treatments in their respective books [1][2][3][30][31][32]. This raises the question on which basis the recommendations had been made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, Domerego and Hainbuch suggested different treatments in their respective books [1][2][3][30][31][32]. This raises the question on which basis the recommendations had been made.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the scientific work of Tekavcic, Porkraichich, and Osmaginich cannot be located in the medical databases at all and the scientific work of Osmanagic refers to melbrosia and complaints during the menopause. Hainbuch [31] referred to a textbook of pharmacopuncture by Kirok Kwon. However, no full text article on a study of pharmacopuncture was found.…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%